2015
DOI: 10.1016/j.pmedr.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to cervical cancer screening varies by human papillomavirus vaccination status in a high-risk population

Abstract: Cervical cancer screening has reduced the incidence of cervical cancer over the past 75 years. The primary aim of this study was to determine if women receiving Gardasil™ (HPV4 vaccine) participated in future cervical cancer screening at the same rate as that observed for unvaccinated women matched on birth year and health care campus. This is a retrospective cohort study of subjects selected from 27,786 females born from 1980 to 1992 who received health care in the Truman Medical Center safety net health syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…Consequently, their findings may not generalize to women in the US. Paynter et al reported a higher level of screening in vaccinated women than in unvaccinated women in a safety net health care system in Kansas City 10 . Using US administrative claim data, Hirth et al reported a positive dose response by number of HPV vaccine received with subsequent Pap screening 9 .…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, their findings may not generalize to women in the US. Paynter et al reported a higher level of screening in vaccinated women than in unvaccinated women in a safety net health care system in Kansas City 10 . Using US administrative claim data, Hirth et al reported a positive dose response by number of HPV vaccine received with subsequent Pap screening 9 .…”
Section: Commentmentioning
confidence: 99%
“…Because the vaccination decision for girls 11–12 years of age is primary made by parents, it is unclear whether the positive association between vaccination and screening behavior we observed here is generalizable to women who first received the vaccine at an earlier age. In fact, Paynter et al reported that women vaccinated closer to age 21 were more likely to get screening than those vaccinated at age 14 10 . Thus, future studies are needed to confirm the association between vaccination in the recommended age range and subsequent screening behavior.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Large population‐based studies in Sweden and the US analyzing the association between HPV vaccination and subsequent cervical cancer screening initiation and compliance with recommended screening intervals have shown that HPV‐vaccinated women were more likely than their unvaccinated counterparts to initiate cervical cancer screening and to adhere to recommended screening intervals. These results highlight a potential emerging disparity in protection among vaccinated and unvaccinated women, with the latter being also less prone to seek and adhere to cancer screening …”
Section: Introductionmentioning
confidence: 91%
“…For these reasons, HPV vaccination does not eliminate the need for cervical cancer screening. The impact of HPV vaccination on cervical cancer screening has been analyzed in various studies most of them demonstrating a positive correlation between HPV vaccination and cervical screening, in spite of a perception that vaccination would lead to patient's reassurance and decreased cervical cancer screening . A population‐based survey in the U.S. showed that 96% of participants were aware of the fact that Pap tests were still needed after vaccination .…”
Section: Introductionmentioning
confidence: 99%